Kaidah Pengulangan Lafaz dalam al-Qur’an: Studi Analisis QS. an-Naml[27]: 60-64 - Dewi Wulandari; Moh.Asror Yusuf; Qoidatul Marhumah (Canonia Religia)
This article aims to examine the meaning of the repetition of phrases (tikrār) found in QS.  an-Naml [27]: 60-64. These verses briefly discuss faith in Allah as a very important teaching and a core aspect of human life. Therefore, it is interesting to explore the meaning of the repetition of phrases implied in the verses that discuss this creed. Some research questions to be answered are: first, what is the meaning of the repetition of phrases in QS. an-Naml [27]: 60-64?; second, what wisdom is contained in this repetition of phrases? The research method used in this study is descriptive-analytical method. Based on the research findings, it is concluded that the meaning of the repetition of phrases in QS. an-Naml [27]: 60-64 is a "confirmation" that is present in the phrase "amman" at the beginning of each verse and signifies a "denial" in the phrase "a‘ilāhun ma'a Allāh" in the middle of the verse, with each repeated five times. The repetition serves as an affirmation of the evidence of Allah's oneness in the face of so many creations in the world, all of which are under Allah's power without the interference of anyone else. The meaning of denial is to negate that anything deserves to be worshiped except Allah alone. Furthermore, the wisdom of the repetition of phrases in Surah an-Naml [27]: 60-64 is aimed at establishing true faith, avoiding acts of polytheism, and as a form of contemplation. Because by repeatedly emphasizing a subject matter, faith becomes firmly entrenched in the minds of every individual.